TO BE CONNECTED: SUPPORTING SELF-REGULATED LEARNING IN HIGHER MUSIC EDUCATION BEFORE AND DURING PANDEMIC - Mutavdžin, Dejana Nenad; Stančić, Milan; Bogunović, Blanka (Psihološka istraživanja, 2021)
In online learning, students are expected to take on more responsibility for their education, and teachers are expected to support students’ self-regulated learning (SRL) skills. In this research, we explore whether young musicians perceive a difference in the actions that the major music teacher (MMT) took, before and during the pandemic, to support their SRL skills and their view on how MMT could further support their learning. The sample included 144 students of the Faculty of Music in Belgrade, who filled in the online inventory, comprised of 24 questions - 17 parallel Likert-type items (referring to MMT’s actions supporting SRL skills, before and during the pandemic), and one was a short letter to the MMT. Data were analyzed using dependent t-test and ANOVA, and reflexive thematic analysis. Students perceived that SRL skills were more encouraged before than during the pandemic. Additionally, our findings show that music students who did not have in-person and online communication, separately, with their MMTs perceived they had lesser support to self-regulate their learning. Findings from qualitative analysis inform educational practice by pointing to specific teacher’s actions that students perceive as important for their further development.